Pretreatment CALLY index as promising novel biomarker in the prediction of surgical and oncological outcomes in esophageal cancer: a multi-center retrospective cohort study - Meng, Peize; Gu, Tongtong; Xu, Jiayong; Huang, Haihua; Jin, Hansong; Wang, Yuchen; Zhang, Hang; Ruan, Zheng (Frontiers in Immunology, 2025)
BackgroundEsophageal cancer (EC) is a global health challenge with high mortality rates. The traditional TNM staging system is limited in its ability to provide accurate prognostic predictions. This study aimed to investigate the utility of the C-reactive protein-albumin-lymphocyte (CALLY) index in the evaluation of mid- to long-term outcomes in patients undergoing esophagectomy.MethodsWe conducted a multi-center retrospective cohort study of 657 EC patients admitted between 2010 to 2024, with 553 patients from Shanghai General Hospital (training cohort) and 104 from Shanghai Sixth People’s Hospital (validation cohort). Associations between the CALLY and overall survival (OS)/disease-free survival (DFS) were evaluated using multivariable-adjusted Cox regression analyses.ResultsPatients with CALLY index > 2.55 were associated with significantly improved OS (adjusted hazard ratio [HR]: 0.55, 95% confidence interval [CI]: 0.43-0.71) and DFS (HR: 0.51, 0.40-0.65), independent of clinical risk factors. Incorporating CALLY index into clinical prediction models significantly enhanced discriminative ability (area under the receiver operating characteristic curve [AUROC] of OS: 0.719-0.752; AUROC of DFS: 0.745-0.788, P < 0.01). In the validation cohort, the same associations were also observed (HR of OS: 0.57, 95% CI: 0.42-0.78; HR of DFS: 0.53, 95% CI: 0.40-0.71). In both cohorts, CALLY index > 2.55 were associated with significantly reduced risk of recurrence.ConclusionsThe CALLY index emerges as a cost-effective prognostic tool integrating inflammation-nutrition-immunity parameters. Its preoperative integration with tumor, node, and metastasis staging and other well-known risk factors might optimize risk stratification and guide personalized therapeutic strategies for EC patients undergoing esophagectomy.